DIFFERENCES IN PHYSIOLOGICAL LOAD OF STUDENTS DURING NORDIC WALKING AND JOGGING - Ivan Ledić; Alem Šabović; Edin Mujanović; Amra Nožinović-Mujanović; Jasmin Mehinović (Sport Scientific And Practical Aspects, 2025)
Physical activity is important for the physical and mental health of almost everyone. Nordic walking is a physical activity in which participants use specially designed poles while walking, while the term jogging implies light running at speeds less than 10 km/h. PURPOSE: The aim of this research is to monitor the load intensity in real conditions, using a heart rate monitor Team Polar System, during nordic walking and jogging and comparing possible differences in heart rate responses after the fifth minute of activity, at an average speed of 7.5km/h. METHODS: The assessment of heart rate responses for this research was conducted on the 30 male students, at 2 separate days. RESULTS: The results of the variables used in this study show statistically significant differences at the level of significance p=.000. From the mean value results (M) it is obvious that the respondents achieved higher results of heart rate responses during nordic walking compared to the identical tests applied during jogging. CONCLUSION: The results of this study indicate that both Nordic walking and jogging are beneficial but Nordic walking contributes more in achieving higher body loads resulting in increased oxygen consumption and thus calories